On the electronic structure and magnetism of CaCrO3: A hybrid-exchange density-functional-theory study. (June 2021) - Chang, Jiawei; Chen, Qiuyuan; Ma, Lin; Li, Chenghan; Peng, Yicheng; Wu, Wei; Wang, Hai
Abstract: Recently the perovskite oxide CaCrO3 has raised concerns for its ground-state electronic structure and magnetic properties. In this report, the hybrid-exchange density functional, PBE0, is used to calculate the electronic structure and magnetic properties of CaCrO3 . The ferromagnetic, A-type anti-ferromagnetic, C-type anti-ferromagnetic, and G-type anti-ferromagnetic states (defined in the text) have been investigated carefully. The computed magnetic ground state has a G-type anti-ferromagnetic configuration (the Néel state). The calculation result is that the nearest-neighboring exchange interactions in the ab -plane and along the c-axis are antiferromagnetic. The next-nearest-neighboring exchange interaction in the ab -plane is much weak but ferromagnetic. We hope this work would shed some light on the controversial ground state of CaCrO3 .